Livestock resources and sustainable development in Africa - Rege, J.E.O.; Bester, J. (New England Univsity, 1998)
Africa is well-endowed with a diverse range of livestock breeds and strains of various species which are vital to the subsistence and economic Development of the continent. They provide year-round flow of essential products, sustain the employment and income of millions of people and contribute draught power and manure for crop production. In the rural areas, livestock are an important source of food and cash, and hence are crucial for the purchase of consumer goods and procurement of farm inputs. They also supply such non-food items as hides, skins, wool, transportation and fuel (from dung), convert crop residues and fibre materials of no value into protein of high quality, serve as a store of wealth and as a means of meeting various social obligations in traditional society and are a major source of revenue and export earnings for many countries. Indigenous livestock provide the only practical means of using vast areas of natural grasslands in regions where crop production is impractical. The importance of indigenous livestock derives from their adaptation and their local availability. In most tropical Africa, sustainable livestock production cannot be guaranteed without the utilization of the adaptive traits of indigenous livestock breeds.